Synthesis, structures, DNA-binding and anticancer activities of some copper(I)-phosphine complexes. (15th January 2019) - Mashat, Khlood H.; Babgi, Bandar A.; Hussien, Mostafa A.; Nadeem Arshad, Muhammad; Abdellattif, Magda H.
Graphical abstract: Copper(I) complexes with a phenanthroline-phosphine set of ligands were synthesized and characterized. The DNA-binding study of the complexes against ct-DNA showed binding constant values that correspond to the intercalation mode of binding, with notable variations in K b due to the different phosphine ligands. The anticancer activities of complexes show the influence of the different phosphine ligands. The data suggested potential anticancer activities against prostate and breast cancers. Molecular docking studies were conducted, highlighting some of the structural-DNA interactions. Abstract: Copper(I) complexes with a phenanthroline-phosphine set of ligands were synthesized by refluxing methanolic solutions of CuBr2 with at least a four fold molar excess of the phosphine ligands, followed by the treatment of the formed {CuBr(PR3 )3 complexes [R = phenyl (1a ), 4-fluorophenyl (1b ), cyclohexyl (1c ) or 4-methoxyphenyl (1d )]} with 1 molar equivalent of 1, 10-phenanthroline in DCM. The tris(4-methoxyphenyl)phosphine ligand afforded the complex [Cu(P[C6 H4 -4-OMe]3 )2 (phen)]Br (2d ), while the other phosphines produced complexes with the general formula CuBr(PR3 )(phen) [R = phenyl (2a ), 4-fluorophenyl (2b ) or cyclohexyl (2c )]. The new complexes were characterized by elemental analysis, 31 P NMR spectroscopy and mass spectrometry. Additional confirmation of the structures of1b, 2b, 2c and2d were determined by single crystal X-ray diffraction. A DNA-binding study of the complexes2a –2d against ct-DNA showed binding constant values that correspond to the intercalation mode of binding. The notable variations in the binding constants of the complexes suggest some contribution from the phosphine ligands. The lipophilicity of the complexes was evaluated theoretically and the calculated log P value of complex2d is positive and high, being in the same range of relatively easy membrane penetrating drugs. The calculated log P values of complexes2a –2c are negative, indicating a low membrane permeability. Complexes2a –2d were examined against four different cancer cell lines. The choice of the phosphine ligand appears to influence the copper(I)-phosphine anticancer activities against the different cancer cell lines. The data suggested that complexes2a and2d show potential anticancer activity against prostate and breast cancers. The four copper complexes were docked against four different proteins associated with prostate or breast cancers activities, highlighting some of the structural-DNA interactions.